Comparative transcriptome analysis, unfolding the pathways regulating the seed-size trait in cultivated lentil (Lens culinaris Medik.) - Dutta, Haragopal; Mishra, Gyan P.; Aski, Muraleedhar S.; Bosamia, Tejas C.; Mishra, Dwijesh C.; Bhati, Jyotika; Sinha, Subodh Kumar; Vijay, Dunna; C. T., Manjunath Prasad; Das, Shouvik; Pawar, Prashant Anupama-Mohan; Kumar, Atul; et al. (Frontiers in Genetics, 2022)
The market class, cooking time, quality, and milled grain yield are largely influenced by the seed size and shape of the lentil (Lens culinaris Medik.); thus, are considered as important quality traits. To unfold the pathways regulating seed size in lentils, transcriptomic approach was performed using a large-seeded (L4602) and a small-seeded (L830) genotypes. The study has generated nearly 375 million high-quality reads, of which 98.70% were properly aligned to the reference genome. Among biological replicates, very high similarity in FPKM (fragments per kilobase of exon per million mapped fragments) values (R>0.9) showed the consistency of RNA-Seq results. Various DEGs (Differentially Expressed Genes) associated mainly with the hormone signaling and cell division pathways, transcription factors, kinases, etc. were identified having role in cell expansion and seed growth. A total of 106,996 unigenes were used for differential expression (DE) analysis. String analysis identified various modules having certain key proteins like Ser/Thr protein kinase, seed storage protein, DNA-binding protein, microtubule associated protein, etc. Additionally, some growth and cell division-related miRNAs like miR3457 (cell wall formation), miR1440 (cell proliferation and cell cycles), and miR1533 (biosynthesis of plant hormones) were identified having role in seed size determination. Using RNA-Seq data, 5254 EST-SSR primers were generated as a source for future studies aiming for the identification of linked markers. In-silico validation using Genevestigator® was done for the Ser/Thr protein kinase, ethylene response factor, Myb transcription factor genes. Interestingly, xyloglucan endotransglucosylase gene was found differentially regulated, suggesting their role during seed development; however, at maturity, no significant differences were recorded for various cell wall parameters including cellulose, lignin, and xylose content. This is the first report in lentil which has unfolded the key seed size regulating pathways and also unveiled a theoretical way for the development of lentil genotypes having customized seed sizes.